2017
DOI: 10.1017/s1551929516001103
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Light Microscopy Using Plasmonic Gratings

Abstract: A novel platform for super-resolution imaging has been devised that employs plasmonic gratings fabricated using glancing angle deposition (GLAD) of silver. GLAD was found to produce a large population of unique nanostructures over the entire plasmonic grating. These nanostructures excite nearby fluorescent molecules to improve spatial resolution to sub-diffraction limit distances while also increasing signal-to-noise ratio (SNR). For example, the improved localization precision produces 65 nm image resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…No noticeable changes in morphology were apparent in the Al NP after heating with 808 nm laser. Previously, we reported that heating of Al NP clusters with 808 nm laser generated a greater heating rate than other wavelengths used in that work [ 52 , 59 ], so the absence of morphology change suggests that no permanent effects (e.g., ignition) occurred during heating with the 808 nm laser at the current laser fluence. This was confirmed by the equivalent image in scattering mode using both polarizer and analyzer at 0° with respect to the grating axis, which revealed depolarization effects due to the metallic content of Al NP.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…No noticeable changes in morphology were apparent in the Al NP after heating with 808 nm laser. Previously, we reported that heating of Al NP clusters with 808 nm laser generated a greater heating rate than other wavelengths used in that work [ 52 , 59 ], so the absence of morphology change suggests that no permanent effects (e.g., ignition) occurred during heating with the 808 nm laser at the current laser fluence. This was confirmed by the equivalent image in scattering mode using both polarizer and analyzer at 0° with respect to the grating axis, which revealed depolarization effects due to the metallic content of Al NP.…”
Section: Resultsmentioning
confidence: 82%
“…These peak locations were blueshifted by about 10 nm with respect to the expected peak locations for dye aggregates in either solution [ 61 , 62 , 63 ] or solid thin films [ 64 ]. We attribute the blueshifted fluorescence emission to the well-documented surface plasmon-coupled emission (SPCE) effect over plasmonic gratings [ 57 , 59 ], whereby the excited state energy of the fluorophore was transferred nonradiatively back to the grating prior to radiative emission by scattering from the grating itself. This process reduced the energy lost to internal conversion within the dye prior to radiative emission and produced a blueshift regardless of other effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver plasmonic gratings were prepared by soft lithography process similar to [19][20][21][22][23]. A silicone stamp was prepared by curing 5:1 ratio Sylgard 1 184 polydimethylsiloxane (PDMS, Gelest) over a halved, cleaned HDDVD for 24 hours at 50 ˚C and 55% relative humidity.…”
Section: Grating Preparationmentioning
confidence: 99%
“…One significant drawback of using fluorescence blinking as a detection modality is the associated signal-to-noise ratio. Recently, our group has developed a cost-effective plasmonic grating platform to detect and analyze chemical and biological molecules down to the SM level using only an upright epi-fluorescence microscope [19][20][21][22][23], replacing expensive total internal reflection (TIR) or confocal optics. Plasmonic gratings rely on a property of noble metals in which they convert incident photons into standing electromagnetic (EM) waves at the surface of the metal-dielectric interface in a process known as surface plasmon resonance (SPR) [24][25][26].…”
Section: Introductionmentioning
confidence: 99%